2016
DOI: 10.7897/2230-8407.07111
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Q-Absorbance Ratio Method for Simultaneous Estimation of Valsartan and Nifedipine in Synthetic Mixture

Abstract: A simple and reliable UV-Spectrophotometry Q-Absorbance ratio method was developed for simultaneous estimation of Valsartan and Nifedipine in synthetic mixture. Q-Absorbance ratio method based on formation of Q-absorbance equation at two wavelengths, one is an isoabsorptive point and another is the λ-max of one of the two drugs. Absorbances are measured at two selected wavelengths, one is 227 nm (Isoabsorptive point) and another being 236 nm (λ-max of NIF). The two drugs comply with Beer-Lambert's law over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Upon reviewing the literature, it has been divulged that binary mixtures of AMX and MET were previously determined using hydrophilic interaction chromatography (HILIC) [ 21 ], UV spectroscopy [ 22 , 23 ] and HPLC [ 24 ]. Also, AMX and MET but this time with famotidine (FAM), an HPTLC report for their analysis in simulated gastric juice was found [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Upon reviewing the literature, it has been divulged that binary mixtures of AMX and MET were previously determined using hydrophilic interaction chromatography (HILIC) [ 21 ], UV spectroscopy [ 22 , 23 ] and HPLC [ 24 ]. Also, AMX and MET but this time with famotidine (FAM), an HPTLC report for their analysis in simulated gastric juice was found [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…An extensive literature survey revealed that few analytical methods such as HPLC, HPTLC, and UV spectrophotometric are available on individual drugs and in combination with other drugs. Literature reveals that only a many few methods like Q‐absorbance UV [20], HPLC [21, 22] method, and so forth are reported for their simultaneous estimation. Hence, the research study focuses on the development and validation of a sensitive, accurate, precise, and simple HPTLC method for simultaneous estimation of IVA and CAR in bulk and pharmaceutical formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous analytical methods for determining ESZ have been developed either alone, or in mixture with other https://aijpms.journals.ekb.eg/ drugs in pharmaceuticals and in biological fluids 27,28 . Limited methods were published for the simultaneous estimation of ASP and ESZ as spectrophotometric 29 , HPTLC 30 , UPLC 31 and HPLC methods 32 . Green analytical chemistry was announced to minimize the hazardous of procedures on workers and the environment.…”
Section: Introductionmentioning
confidence: 99%